Method for repairing CFRP composite material through in-situ resistance heating
By introducing a thermoplastic repair interlayer between CFRP composite materials and using resistance heating to repair damage to CFRP composite materials, the problem of difficult detection and repair of interlayer damage is solved, and efficient and low-cost structural performance recovery is achieved.
Patent Information
- Application Number
- CN202510711493.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-29
- Publication Date
- 2025-09-16
AI Technical Summary
The interlaminar mechanical properties of CFRP composite materials are weak, and delamination is a common failure mode. Damage is difficult to detect and time-consuming and labor-intensive to repair, seriously affecting its service life.
A thermoplastic repair interlayer was introduced between the CFRP composite material layers. EMAA_CNT and EMAA_CNT-COOH were prepared by a casting process. Metal foil was pasted with conductive adhesive as an electrode. Current and pressure were applied for in-situ resistance heating to repair the damaged cracks.
It improves the interlaminar fracture toughness, has high repair efficiency and low cost, is suitable for on-site repair, and restores the structural properties of the composite material. The maximum bending strength and interlaminar shear strength recovery rate exceeds 85%.
Smart Images

Figure CN120645473A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of resistance heating repair, and in particular relates to a method for repairing CFRP composite materials by in-situ resistance heating. Background Art
[0002] Due to its lightweight, high strength, fatigue resistance, and corrosion resistance, CFRP is widely used in civil engineering, aerospace, sports and leisure, vehicles, and ships. However, the widespread application of CFRP composites also faces certain challenges. Laminated CFRP composites have weak interlaminar mechanical properties, and delamination is one of the most common failure modes of engineering structures made from this composite material. Furthermore, interlaminar damage is difficult to detect, making its location and repair time-consuming and labor-intensive. Delamination failure significantly reduces the service life of CFRP. To extend the service life of CFRP composites, interlaminar damage repair has been a hot topic in CFRP composite research.
[0003] Damage repair strategies can significantly extend the service life of CFRP composites and effectively address structural damage problems that are difficult to access due to their special location, such as delamination damage inside wind turbine blades. In this way, the frequency of part replacement is greatly reduced, and maintenance costs are significantly reduced, which not only brings positive benefits to economic development, but also effectively reduces resource waste. For traditional thermal repair methods, the repair process is often completed with the help of heating equipment. If cracks appear locally in a large composite structure, it is difficult to heat the entire structure, and the integrity of the structure may be damaged. Repairing cracks through in-situ local heating methods can overcome existing limitations. After introducing a thermoplastic repair interlayer into the carbon fiber reinforced composite material, with the help of the excellent conductivity of carbon fiber fabric and CNT, cracks in the CFRP composite material can be repaired in situ through local resistance heating methods.
[0004] Through the above analysis, the problems and defects of the existing technology are as follows:
[0005] Laminated CFRP composites have weak interlaminar mechanical properties, making delamination one of the most common failure modes in engineering structures made with this composite material. Furthermore, interlaminar damage is difficult to detect, making it time-consuming and labor-intensive to locate and repair. Delamination failure significantly reduces the service life of CFRP. To extend the service life of CFRP composites, interlaminar damage repair has been a hot topic in CFRP composite research. Summary of the Invention
[0006] In view of the problems existing in the prior art, the present invention provides a method for repairing CFRP composite materials by in-situ resistance heating.
[0007] The present invention is achieved by providing a method for repairing CFRP composite materials by in-situ resistance heating, comprising:
[0008] Step 1: EMAA_CNT and EMAA_CNT-COOH thermoplastic repair interlayers were prepared using EMAA pellets, CNT and CNT-COOH through a casting process;
[0009] Step 2: Laying the thermoplastic repair interlayer prepared in step 1 between the carbon fiber fabric layers, and preparing CFRP / EMAA_CNT and CFRP / EMAA_CNT-COOH composites through the VARIM process;
[0010] Step 3: Use conductive glue to stick metal foil as an electrode on the damaged composite material, apply current to the composite material, and apply 0-3MPa pressure to the composite material at the same time; the current makes the temperature of the composite material reach 80-200℃, and maintain it for 15-120 minutes to repair the damaged cracks.
[0011] Furthermore, in step 1, the preparation method of the thermoplastic repair interlayer is as follows:
[0012] Step 1.1: Using a twin-screw extruder and micro-cast film forming system, EMAA pellets are mixed with CNT and CNT-COOH at a temperature of 100-200°C and a screw speed of 80-120 rpm for 10-30 minutes, followed by extrusion and casting into films;
[0013] In the step 1.1, CNT and CNT-COOH each account for 0-5 wt% of the mass fraction of the thermoplastic repair interlayer.
[0014] Furthermore, in step 1.1, the thickness of the thermoplastic repair interlayer is 30-300 μm.
[0015] Furthermore, in step 2, the volume fraction of the carbon fiber in the composite material is 50-60 vol%, the volume fraction of the epoxy resin is 40-50 vol%, and the carbon fiber fabric in the composite material has 8-24 layers.
[0016] Furthermore, in step 3, an electric current may be applied to the entire composite material or a local area thereof, and the applied electric current may be direct current or alternating current.
[0017] Furthermore, in step 3, the metal foil used as the electrode is one or more of copper foil and aluminum foil.
[0018] Another object of the present invention is to provide a system for in-situ resistance heating repair of CFRP composite materials, comprising:
[0019] A thermoplastic repair interlayer preparation module is used to prepare EMAA_CNT and EMAA_CNT-COOH thermoplastic repair interlayers using EMAA pellets, CNT and CNT-COOH through a casting process;
[0020] Composite material preparation module, used to lay the prepared thermoplastic repair interlayer between carbon fiber fabric layers and prepare CFRP / EMAA_CNT and CFRP / EMAA_CNT-COOH composite materials through VARIM process;
[0021] The repair module is used to use conductive glue to stick metal foil as an electrode on the damaged composite material, apply current to the composite material, and apply 0-3MPa pressure to the composite material at the same time; the current makes the temperature of the composite material reach 80-200℃, and maintain it for 15-120 minutes to repair the damaged cracks.
[0022] In combination with the above technical solutions and the technical problems solved, the advantages and positive effects of the technical solutions to be protected by the present invention are as follows:
[0023] 1. In the present invention, the resistance heating repair process is carried out by applying direct current to the composite material using a DC power supply. Compared with the traditional heating repair method, the in-situ resistance heating repair method has low energy consumption.
[0024] 2. By implanting a thermoplastic repair interlayer between CFRP composite material layers, on the one hand, the interlaminar fracture toughness of CFRP can be improved; on the other hand, the thermoplastic repair interlayer components can undergo chemical or physical reactions with the matrix resin to re-bond the cracks, thereby achieving the purpose of repairing damaged cracks.
[0025] 3. The present invention has the characteristics of low production cost, high raw material utilization rate and simple preparation method.
[0026] The present invention provides a method for repairing damaged cracks between CFRP composite layers using in-situ resistance heating. This method introduces a thermoplastic repair interlayer (EMAA_CNT and EMAA_CNT-COOH) between the CFRP composite layers. The resulting composite materials are designated CFRP / EMAA_CNT and CFRP / EMAA_CNT-COOH, respectively. When cracks develop between the composite layers under external load, direct current (DC) is applied to the composite, generating Joule heat that melts the thermoplastic repair interlayer and rebonds the crack, achieving the desired repair. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a flow chart of a method for repairing CFRP composite materials by in-situ resistance heating provided by an embodiment of the present invention.
[0028] Figure 2This is a system structure block diagram of the in-situ resistance heating repair of CFRP composite materials provided by an embodiment of the present invention.
[0029] Figure 3 This is a diagram showing the distribution of CNT and CNT-COOH in the EMAA matrix by SEM characterization of the prepared EMAA_CNT and EMAA_CNT-COOH thermoplastic repair interlayers provided in an embodiment of the present invention.
[0030] Figure 4 This is a test process diagram of performing a DCB test on the prepared CFRP / EMAA_CNT and CFRP / EMAA_CN T-COOH composite materials to produce delamination damage provided by an embodiment of the present invention.
[0031] Figure 5 This is a graph of repair temperature and DC power provided by an embodiment of the present invention.
[0032] Figure 6 The interlaminar fracture toughness (G) of the CFRP / EMAA_CNT and CFRP / EMAA_CNT-COOH composite materials before (V) and after (R) repair provided by the embodiment of the present invention is IC ) and repair efficiency (RE) summary graph. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0034] In traditional CFRP composite structural repair, crack repair often relies on autoclave processes or external heating equipment. These processes are complex, energy-intensive, and poorly localized, making it difficult to achieve in-situ repair of components while they are still in service. These repair methods generally require complete disassembly, transfer, cleaning, and re-solidification, severely limiting the efficient maintainability of carbon fiber reinforced composites in fields such as aviation, automotive, and wind energy. Traditional thermosetting repairs, in particular, struggle to provide continuous repair interface bonding when faced with substructural damage such as fine cracks and interlaminar delamination, posing the risk of secondary fatigue cracking.
[0035] This invention incorporates a thermoplastic repair interlayer during the composite material manufacturing stage. This interlayer, a conductive, meltable, and interfacially affinitive repair layer, is formed by blending EMAA-based CNT or CNT-COOH nanofillers. This creates a "self-healing core" at the material's constitutive level. The thermoplastic polymer exhibits reversible melt flowability, and the CNT filler imparts localized Joule heating. Applying an electric current to the cracked area causes the thermoplastic interlayer to locally heat, soften, flow, fill, and resolidify, sealing the defect and rejoining the interface. This process requires no changes to the overall structure, offering true "in-situ, self-heating, and no disassembly required" engineering adaptability.
[0036] The conductive path is established by attaching metal foil electrodes to the damaged area, using conductive adhesive as the contact medium. When current is applied, the CNTs in the interlayer form a microscale resistor network. Regions of higher current density within the interlayer heat up first, driving increased polymer chain activity, triggering viscoelastic deformation, adhesive diffusion, and interfacial healing. The application of pressure increases the contact density between the damaged interfaces and the degree of coverage at the interlayer-carbon fiber interface, synergistically achieving structural performance recovery.
[0037] The temperature control and power-on time window are set based on the EMAA melting transition range (approximately 90–100°C) and the uniformity of CNT-CNT thermal conductivity distribution. Heating within the 80–200°C range allows for flexible adaptation to varying crack sizes and depths. By adjusting the power density and power-on duration, the melting range and repair layer thickness can be precisely controlled, preventing the heat-affected zone from spreading to the adjacent fiber / matrix interface and effectively controlling the mechanical property degradation caused by thermal degradation and the glass transition of the resin matrix.
[0038] The overall repair process can be performed under laboratory field conditions, without the need for high-pressure vessels or large equipment. Requiring only a standard power supply, a pressure-loading mechanism, and a contact electrode module, the process offers advantages in field availability, repeatability, and affordability. The thermoplastic repair interlayer performs multiple functions during the repair process, including interface reconstruction, microcrack closure, and stress transfer path reconstruction, providing efficient compensation for subsequent structural mechanical loads. A comparison of the mechanical properties of the composite material before and after damage indicates that the maximum flexural strength and interlaminar shear strength recovered by over 85% after repair, demonstrating excellent structural recovery capabilities.
[0039] The essential innovation of this in-situ resistance heating repair technology lies in the coordinated design of embedded repair materials and local energy input throughout the entire process of "materials-preparation-electrical heating-interface reconnection", fundamentally breaking through the repair bottleneck of traditional CFRP thermosetting structures that are difficult to reconstruct the interface, and realizing intelligent adaptive repair of carbon fiber composite materials in service status, providing an advanced technical path for the application of high-reliability, low-maintenance composite materials.
[0040] like Figure 1As shown, an embodiment of the present invention provides a method for repairing CFRP composite materials by in-situ resistance heating, comprising the following steps:
[0041] S101: preparing EMAA_CNT and EMAA_CNT-COOH thermoplastic repair interlayers using EMAA pellets, CNT and CNT-COOH through a casting process;
[0042] S102: Laying the thermoplastic repair interlayer prepared in S101 between the carbon fiber fabric layers to prepare CFRP / EMAA_CNT and CFRP / EMAA_CNT-COOH composite materials through a VARIM process;
[0043] S103: Use conductive adhesive to stick metal foil on the damaged composite material as an electrode, apply current to the composite material, and apply 0-3MPa pressure to the composite material; the current makes the temperature of the composite material reach 80-200℃, and maintain it for 15-120 minutes to repair the damaged cracks.
[0044] In S101 provided in an embodiment of the present invention, the method for preparing the thermoplastic repair interlayer is as follows:
[0045] Step 1.1: Using a twin-screw extruder and micro-cast film forming system, EMAA pellets are mixed with CNT and CNT-COOH at a temperature of 100-200°C and a screw speed of 80-120 rpm for 10-30 minutes, followed by extrusion and casting into films;
[0046] In the step 1.1, CNT and CNT-COOH each account for 0-5 wt% of the mass fraction of the thermoplastic repair interlayer.
[0047] In step 1.1 provided in an embodiment of the present invention, the thickness of the thermoplastic repair interlayer is 30-300 μm.
[0048] In S102 provided in the embodiment of the present invention, the volume fraction of carbon fiber in the composite material is 50-60 vol%, the volume fraction of epoxy resin is 40-50 vol%, and the carbon fiber fabric in the composite material has 8-24 layers.
[0049] In S103 provided in the embodiment of the present invention, current may be applied to the entire composite material or a local area thereof, and the applied current may be direct current or alternating current.
[0050] In S103 provided in the embodiment of the present invention, the metal foil used as the electrode is one or more of copper foil and aluminum foil.
[0051] like Figure 2 As shown, an embodiment of the present invention provides a system for repairing CFRP composite materials by in-situ resistance heating, comprising:
[0052] A thermoplastic repair interlayer preparation module is used to prepare EMAA_CNT and EMAA_CNT-COOH thermoplastic repair interlayers using EMAA pellets, CNT and CNT-COOH through a casting process;
[0053] Composite material preparation module, used to lay the prepared thermoplastic repair interlayer between carbon fiber fabric layers and prepare CFRP / EMAA_CNT and CFRP / EMAA_CNT-COOH composite materials through VARIM process;
[0054] The repair module is used to use conductive glue to stick metal foil as an electrode on the damaged composite material, apply current to the composite material, and apply 0-3MPa pressure to the composite material at the same time; the current makes the temperature of the composite material reach 80-200℃, and maintain it for 15-120 minutes to repair the damaged cracks.
[0055] The present invention employs a method for in-situ repair of cracks in CFRP composite materials by implanting a thermoplastic interlayer of EMAA_CNT and EMAA_CNT-COOH between CFRP composite layers. The interlayer is produced using a twin-screw extrusion and micro-cast film molding system. This interlayer is then implanted into the CFRP composite using a VARIM process.
[0056] Furthermore, the CFRP / EMAA_CNT and CFRP / EMAA_CNT-COOH composite materials include the following components: a 50-60 μm thick thermoplastic repair layer of EMAA_CNT and EMAA_CNT-COOH, comprising 5 wt% CNT and CNT-COOH and 95 wt% EMAA. The CFRP composite material contains 52-53 vol% carbon fiber and 47-48 vol% epoxy resin.
[0057] Furthermore, the CNT and CNT-COOH are tubular carbon nanomaterials with diameters of 10-20 nm and lengths of 5-15 μm, and the carboxyl content in the CNT-COOH is greater than 0.5 mmol / g.
[0058] Furthermore, the EMAA pellets have a diameter of about 5 mm and a carboxyl content of 19 wt%.
[0059] Furthermore, the carbon fiber fabric has a surface density of 200 g / m 2 plain weave fabric.
[0060] Furthermore, the epoxy resin is bisphenol A epoxy resin, and the mass ratio of the resin to the curing agent is 100:34.
[0061] Furthermore, the preparation method of the EMAA_CNT and EMAA_CNT-COOH thermoplastic repair interlayer comprises the following steps:
[0062] In the first step, the EMAA pellets were dried in an oven at 50°C for 12 h to remove the moisture contained therein.
[0063] In the second step, EMAA-CNT and EMAA-CNT-COOH thermoplastic repair interlayers were prepared using a twin-screw extrusion and micro-cast film forming system. EMAA pellets were mixed with CNT and CNT-COOH, respectively, at a mixing temperature of 150°C and a screw speed of 100 rpm for 10 minutes before extrusion and casting into films. The casting die temperature was 150°C, the die width was 65 mm, the extrusion speed was 20 rpm, the take-off and stretching roll speeds were 300 mm / min, and the take-up roll speed was 80 rpm.
[0064] Furthermore, composite molding: CFRP / EMAA_CNT and CFRP / EMAA_CNT-COOH composites were prepared by VARIM process.
[0065] The first step is the laying of carbon fiber fabric and interlayer: 16 layers of carbon fiber fabric are placed in a vacuum bag, and the prepared thermoplastic repair interlayer and PTFE membrane are inserted into the middle layer of the carbon fiber fabric (the eighth and ninth layers of glass fiber fabric), respectively.
[0066] The second step, VARIM process, involves injecting epoxy resin solution under a vacuum pressure of 0.09 MPa. The epoxy resin and curing agent are thoroughly mixed at a mass ratio of 100:34, then cured at 60°C for 4 hours and then at 150°C for 2 hours, followed by natural cooling to room temperature.
[0067] The third step is cutting of CFRP / EMAA_CNT and CFRP / EMAA_CNT-COOH composites: the composites are cut into 140 mm × 19 mm DCB specimens using an engraving machine.
[0068] Furthermore, damage preparation and in-situ resistance thermal repair of CFRP / EMAA_CNT and CFRP / EMAA_CNT-COOH composites:
[0069] The first step, damage preparation: interlaminar cracks of CFRP / EMAA_CNT and CFRP / EMAA_CNT-COOH composites were generated by DCB testing, and the interlaminar fracture toughness was calculated based on the test results.
[0070] The second step involves in-situ resistance heating repair: Conductive silver glue is used to attach copper foil electrodes to both ends of the crack in the delaminated composite material. Two thermocouples are connected to the top and bottom surfaces of the composite material to monitor temperature. A pressure of 0.03 MPa is applied to the composite material to ensure contact between the fracture surfaces. The resistance heating repair process is performed by applying direct current to the composite material using a DC power supply. This method allows for in-situ resistance heating repair of the composite material.
[0071] Technical effect:
[0072] 1. The distribution of CNT and CNT-COOH in the EMAA matrix was characterized by SEM on the prepared EMAA_CNT and EMAA_CNT-COOH thermoplastic repair interlayers. Figure 3 As shown in Figure 2, at a concentration of 0.5 wt%, the two CNTs are evenly dispersed without obvious agglomeration. Figure 3 As shown in a and d. As the CNT concentration increases, the agglomeration of CNTs can be clearly found, as shown in Figure 3 In addition, CNT-COOH in the EMAA membrane is less aggregated than non-carboxylated CNT.
[0073] 2. DCB test was performed on the prepared CFRP / EMAA_CNT and CFRP / EMAA_CNT-COOH composites to produce delamination damage. The test process is as follows: Figure 4 shown.
[0074] 3. Use conductive silver glue to stick copper foil as electrodes at both ends of the crack in the delaminated composite material, connect two thermocouples to the top and bottom surfaces of the composite material to monitor the temperature, and apply a pressure of 0.03MPa to the composite material to ensure that the fracture surfaces are in contact with each other. The resistance heating repair process is carried out by applying direct current to the composite material using a DC power supply. This method can achieve in-situ resistance heating repair of the composite material. The temperature of the composite material will affect the resistance change, so the DC power needs to be adjusted to control the temperature during the repair process. The repair temperature and DC power curves are shown in Figure 2. Figure 5 The repair process can be divided into four stages based on temperature changes: the first stage is a rapid temperature rise stage with a temperature change rate of approximately 15.8°C / min; the second stage is a slower temperature rise rate of approximately 1.1°C / min; the third stage reaches 150°C and is maintained for 30 minutes; the fourth stage is a cooling stage, in which the DC power is turned off and the device is allowed to cool naturally to room temperature.
[0075] 4. Interlaminar fracture toughness (G) of CFRP / EMAA_CNT and CFRP / EMAA_CNT-COOH composites before (V) and after (R) repair IC ) and repair efficiency (RE) are summarized in Figure 6At the same CNT concentration, the RE of the CFRP / EMAA_CNT-COOH composite is higher than the RE and repair efficiency of CFRP / EMAA_CNT. When the CNT-COOH concentration in the EMAA_CNT-COOH thermoplastic repair interlayer is 5wt%, the RE is 325%, which demonstrates the feasibility of this repair strategy.
[0076] Example 1
[0077] EMAA was mixed with 2 wt% carbon nanotubes (CNTs) and blended at 150°C for 20 minutes using a twin-screw extruder. The resulting EMAA-CNT thermoplastic repair layer was then formed into a 50 μm-thick film using a micro-cast film machine. This film was then sandwiched between 12 layers of T700 carbon fiber plain weave fabric. An epoxy matrix resin was then injected using the VARIM process to form a CFRP / EMAA-CNT composite sheet with a carbon fiber volume fraction of approximately 55%, measuring 300 mm × 300 mm × 2.5 mm.
[0078] After prefabricating an interlaminar crack approximately 50 mm long in the center of the composite material sample, copper foil (20 μm thick) was attached to the upper and lower surfaces of the crack, and the electrode connections were secured using conductive silver glue. A 10A DC current was applied through a constant current source for 5 minutes, raising the interlayer temperature to 150°C while simultaneously applying a pressure of 0.03 MPa. The thermoplastic interlayer softened and flowed under the current heating, completing the interface filling and connection in the crack area. After cooling and solidification, a re-bonded structure was formed.
[0079] Infrared thermal imaging and scanning electron microscopy analysis showed that the repair layer in the crack area was fully filled and tightly bonded to the substrate, with no voids or interface failure areas, verifying the effectiveness of the in-situ heating repair process in terms of macro-mechanics and microstructure.
[0080] Example 2
[0081] EMAA was blended with 1 wt% CNT-COOH at 170°C and a screw speed of 100 rpm for 25 minutes before casting to produce a 200 μm thick EMAA-CNT-COOH film. This film was embedded between 16 layers of T800 carbon fiber cloth and then formed into a composite plate (300 mm × 300 mm × 3 mm) using VARIM molding. The carbon fiber volume fraction was 58%. Artificial impact damage (10 mm diameter low-velocity impact) was introduced at the edge of the composite plate to construct a typical impact crack damage model.
[0082] Aluminum foil electrodes were attached to the surface and connected to a controllable pulse power supply. The peak pulse current was set to 6A for 30 minutes. The center of the composite material was heated to 200°C while applying an external pressure of 2 MPa. This caused the interlayer to melt rapidly, and the polar groups reinforced by the CNT-COOH interacted strongly with the epoxy resin interface, forming a stable recombination interface. The repair was then allowed to cool for 30 minutes.
[0083] The above description is only a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with this technical field within the technical scope disclosed by the present invention and within the spirit and principles of the present invention should be covered by the scope of protection of the present invention.
Claims
1. A method for repairing CFRP composite materials by in-situ resistance heating, characterized in that: The following steps are involved: Step 1: preparing a thermoplastic repair interlayer, blending EMAA pellets with carbon nanotubes and carboxylated carbon nanotubes, and forming an EMAA-based thermoplastic repair interlayer through a casting process; Step 2: Laying the thermoplastic repair interlayer between carbon fiber fabric layers, and preparing a thermoplastic layer sandwich composite material by a resin transfer molding process; Step 3: Paste metal foil as an electrode on the damaged part of the composite material, bond it with conductive glue, apply current to the composite material, heat it to 80-200℃, and keep it warm for 15-120 minutes under 0-3MPa pressure at the same time to achieve thermoplastic self-healing repair of the cracks.
2. The method for repairing CFRP composite materials by in-situ resistance heating according to claim 1, characterized in that: The thermoplastic repair interlayer in step 1 is prepared by twin-screw extrusion combined with cast film molding. Under the conditions of a temperature of 100-200° C. and a screw speed of 80-120 rpm, EMAA pellets and carbon nanotubes are mixed for 10-30 minutes and then extruded into a film.
3. The method for repairing CFRP composite materials by in-situ resistance heating according to claim 2, characterized in that: The total mass of the carbon nanotubes and the carboxylated carbon nanotubes in the thermoplastic repair interlayer accounts for 0-5% of the thermoplastic interlayer.
4. The method for repairing CFRP composite materials by in-situ resistance heating according to claim 1, characterized in that: The thickness of the thermoplastic repair interlayer is 30-300 μm.
5. The method for repairing CFRP composite materials by in-situ resistance heating according to claim 1, characterized in that: The volume fraction of carbon fiber in the composite material is 50-60 vol%, the volume fraction of epoxy resin is 40-50 vol%, and the number of carbon fiber fabric layers is 8-24.
6. The method for repairing CFRP composite materials by in-situ resistance heating according to claim 1, characterized in that: The current applied in step 3 may be direct current or alternating current, and the current only acts on the entire composite material or a local area.
7. The method for repairing CFRP composite materials by in-situ resistance heating according to claim 1, characterized in that: The electrodes are made of copper foil or aluminum foil.
8. An in-situ resistance heating repair system for implementing the in-situ resistance heating repair method for CFRP composite materials according to any one of claims 1 to 7, characterized in that: include: Thermoplastic interlayer preparation module, used to mix EMAA and carbon nanotube materials and form an interlayer through a casting film process; A composite manufacturing module for embedding interlayers into multiple layers of carbon fiber fabric and forming composite panels through vacuum-assisted resin transfer molding; The in-situ heating repair module includes a power control device, an electrode metal foil fixing mechanism and a pressure application structure, which can realize temperature-controlled power repair of damaged parts.
9. The system according to claim 8, wherein The metal electrode in the in-situ heating repair module is copper foil or aluminum foil with a thickness of 10-50 μm, and is adhered to the surface of the damaged part by conductive glue.
10. The system according to claim 8, wherein The power-on control device includes an adjustable constant current source and a temperature control feedback closed-loop circuit, which is used to control the repair temperature within the range of 80-200°C.